Properties of mandi bunga (flowering bath) as Malaysian tradition practice / S. Roslan and Rafeah Legino - Roslan, S.; Legino, Rafeah (2016)
Mandi bunga (flowering bath) as a part of a Malaysian traditional practice such as to maintain general health, the bride in marriage, reduces stress and others. The properties of flowers actually are internal beauty treatments practiced by peoples can get the calmness feeling after the treatments is done. The major circumstance for these practices is taken from Al- Quran and Sunnah Hadis (sunnah from hadith) also known as Islam therapy. Furthermore, the research to study the properties of mandi bunga (flowering bath) is good for health like from the aromatherapy of flower, colors, water mixture of flowers and others. This is good because it is natural and organic. The appropriate process, which analyses related document and visual analysis was delivered. The classification of several images that was engaged with suitable theme and style in how the idea and the artwork have been proposed. This study will be interlinked with today's development and progress which is focused towards the properties of mandi bunga (flowering bath) as a Malay tradition which still in practice such as in Spa (saloon). The findings show that the advertisement gives a majoring factor that influences the individual practice of daily life to care about health. The artwork actually represents the visual feeling of calmness of the society and also promoting the properties of mandi bunga (flowering bath) from Malay tradition practice and Islamic therapy also has aromatherapy treatments with natural and organic product to people using it.